Home Care Edukasi pada Mahasiswa Semester II dengan Perawatan Luka - Rizki Yeni Wulandari; Hardono Hardono; Nuria Salsabila; Hidayatus Sholiha; Anggun Anggun; Nuraini Nuraini; Rahmi Nabilah; Muhamad Dhenda Raihan; Elpa Putri Agista; Fenti Dwi Kusuma Ningrum (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service activity aimed to improve the knowledge, attitudes, and skills of second-semester nursing students at Universitas Aisyah Pringsewu in home care-based wound care. The methods included education, demonstration, and hands-on practice of wound care according to standard operating procedures (SOP) involving 50 students. Evaluation was conducted using pre-test and post-test. The results showed significant improvements in all aspects. Students' knowledge increased, for example, understanding of 0.9% NaCl solution rose from 50% to 90%. Positive attitudes toward wound care also improved, with almost all respondents expressing willingness to perform proper wound care. In terms of practice, correct handwashing and wound cleaning behaviors increased to above 85%. The combination of education, demonstration, and hands-on practice proved effective in enhancing nursing students' competencies.